Inequalities in neighbourhood features within children's 20-minute neighbourhoods and variation in time spent locally, measured using GPS - Olsen, Jonathan R (Wellbeing Space Soc, 2023)
There has been a growing interest in policies that encourage local living by promoting accessible and walkable communities, such as the 20-minute neighborhood concept. Despite the widespread adoption of this policy worldwide, little research has been conducted on the characteristics of children's 20-minute neighborhoods and their association with time spent locally. This study aimed to explore the features of Scottish children's 20-minute neighborhoods by analysing an 800 m road and path network buffer surrounding 687 children's homes. Based on existing literature, the study identified key features associated with children's time spent locally and the 20-minute neighborhood policy. The study then examined variations in these features by socioeconomic status, urbanicity, and gender. The findings revealed significant inequalities in the presence of health-benefiting (e.g., green spaces, recreational facilities, healthy food outlets) and health-harming (e.g., major roads, unhealthy commodity retailers) environments within children's 20-minute neighborhoods. Children from more deprived areas had access to more of both types of environments. The study also found that having a school within a 20-minute neighborhood was associated with an increased amount of time spent locally (IRR 1.62, 95% CI 1.5 to 1.8, p<0.001). The study suggests that the 20-minute neighborhood policy should extend beyond mere access to local amenities and prioritise creating healthy 20-minute neighborhoods, particularly in socioeconomically deprived areas. The research highlights the importance of promoting equal access to quality local environments, which can contribute to improved health and well-being outcomes for children.